2022
DOI: 10.3389/fmed.2022.1017650
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis and mitochondrial homeostasis: The crossroads of metabolism and immunity

Abstract: Rheumatoid arthritis is an autoimmune disease characterized by chronic symmetric synovial inflammation and erosive bone destruction. Mitochondria are the main site of cellular energy supply and play a key role in the process of energy metabolism. They possess certain self-regulatory and repair capabilities. Mitochondria maintain relative stability in number, morphology, and spatial structure through biological processes, such as biogenesis, fission, fusion, and autophagy, which are collectively called mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 153 publications
0
11
0
Order By: Relevance
“…78 This process primarily encompasses mitochondrial biogenesis, altered dynamics, and autophagy. 79 Impaired mitochondrial biogenesis, resulting from the loss of mitochondrial DNA, has been implicated in RA development. Reduced mitochondrial autophagy prevents timely clearance of dysfunctional mitochondria, thereby exacerbating the onset of RA.…”
Section: Mitochondrial Homeostasismentioning
confidence: 99%
“…78 This process primarily encompasses mitochondrial biogenesis, altered dynamics, and autophagy. 79 Impaired mitochondrial biogenesis, resulting from the loss of mitochondrial DNA, has been implicated in RA development. Reduced mitochondrial autophagy prevents timely clearance of dysfunctional mitochondria, thereby exacerbating the onset of RA.…”
Section: Mitochondrial Homeostasismentioning
confidence: 99%
“…These factors can activate FLSs and mediate proliferation, anti-apoptosis, erosion, migration, and other pathological behaviors ( 53 , 54 ). Mitochondrial damage and oxidative stress can affect immune cell metabolic processes and promote inflammatory behavior ( 55 , 56 ). Additionally, ROS and the products of mitochondrial damage are good activators of inflammatory response.…”
Section: Role Of Ros and Mitochondrial Damage In Ra Inflammationmentioning
confidence: 99%
“…The mitochondrion is a semi-autonomous organelle with a double membrane structure, which can provide cell energy through the tricarboxylic acid cycle (TCA) oxidative phosphorylation ( 11 , 12 ). Previous studies have found that imbalances in mitochondrial homeostasis may contribute to the development of various autoimmune diseases including RA, scleroderma, desiccation syndrome and systemic lupus erythematosus ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%